DESIGN, CONSTRUCTION AND PERFORMANCE EVALUATION OF A COCO PEAT BLOCK MAKING MACHINE - S. Tam-awen , Zion Jemillinium; Piscador, Rackielyn B; Afuyog, Mirafel T (MATTER: International Journal of Science and Technology, 2019)
The coco peat block making machine is comprised of a compressing rod assembly, mold box, prime mover, and frame with a pair of wheels enabling easier transportability of the machine. Coco peat of different moisture contents (11-14%; 15-18%; and 19-22%) were compressed at different compressing ratios (4:1; 5:1; and 6:1) using the designed and fabricated machine. The study was conducted to (1) evaluate the blocking capacity; (2) establish the moisture content range and compression ratio of blocking; (3) determine the bulk density of the blocked coco peat; and (4) perform a simple cost analysis of the machine. The results showed that the moisture content range and compression ratio have significant effect on the coco peat block recovery and blocking capacity. The operating parameters in blocking the coco peat were established at a moisture content of 15-18% MC and compression ratio of 4:1 giving a blocking capacity of 68.32 blocks per hour.